'Fading Crimean Flowers': Spasmodic Sonnets on the War. (July 2018) - Willett, Mischa
Abstract : In their refusal to aestheticise Crimean warfare, as most of their fellow poets and newspapermen had done, Sydney Dobell and Alexander Smith, in the co-authored Sonnets on the War (1855) present a harrowing picture of the conflict from myriad viewpoints, all of which deny the patriotism and hawkishness implicit in glamorising armed conflict. This poly-vocalic collection pushes more boundaries than has previously been noticed. The choice of form, itself a commentary – this is not a war fit for epic – the emphasis on women's roles, and the anonymous and ventriloquised voicing announce departures from conventions of martial verse, and also from what we have heretofore understood about these poets' careers.